Reflective Focusing Based on Few-Layer Gradient Metasurface Element Array - Yan, Mengyao; Sun, Zhichao; Wu, Bairui; Cheng, Pan; Xu, Bijun (Frontiers in Physics, 2020)
This study proposes a three-layer focusing gradient metasurface for wavefront processing. The structure works in the frequency range of 15 to 25 GHz, and has a central frequency of 19.6 GHz. The metasurface unit is organized in a square and has high-impedance elements that reflect the full range of phase shifts. When the microwave beam is incident on this metasurface, the high-impedance elements modulate the beam according to the gradient arrangement, to realize the focusing effect of the lens, and the efficiency reaches 82%. The simulation results are consistent with the theoretical results.